2018
DOI: 10.1007/s10946-018-9738-9
|View full text |Cite
|
Sign up to set email alerts
|

Trajectory-Based Interpretation of Laser Light Diffraction by a Sharp Edge

Abstract: In the diffraction pattern produced by a half-plane sharp edge when it obstructs the passage of a laser beam, two characteristic regions are noticeable. There is a central region, where it can be noticed the diffraction of laser light in the region of geometric shadow, while intensity oscillations are observed in the non-obstructed area. On both sides of the edge, there are also very long light traces along the normal to the edge of the obstacle. The theoretical explanation to this phenomenon is based on the F… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…The experimental observations show the opposite; and thus, the trajectory theory is challenged. Note that there is a "tail" on the left side of the zeroth-order-fringe, which is due to the diffraction of the edge of the blocker [30].…”
Section: Experiments Testing Trajectory Theory: Shield Contacting Diaphragm Of Double Slitmentioning
confidence: 99%
“…The experimental observations show the opposite; and thus, the trajectory theory is challenged. Note that there is a "tail" on the left side of the zeroth-order-fringe, which is due to the diffraction of the edge of the blocker [30].…”
Section: Experiments Testing Trajectory Theory: Shield Contacting Diaphragm Of Double Slitmentioning
confidence: 99%
“…[ 28,29 ] A recent investigation has confirmed that the vignetting profile is linear to first order, with higher order effects leading to oscillations about the linear slope. [ 30 ] These oscillations become higher in frequency and lower in amplitude with increasing photon energy. Therefore, in the X‐ray regime the linear functional is a very good approximation.…”
Section: Vignettingmentioning
confidence: 99%
“…Actually, this can readily be done if the role of the probability density is identified with the electromagnetic energy density, and the quantum density current or quantum flux [6] with the Poynting vector [7][8][9]. This prescription, where the corresponding electromagnetic streamlines or rays describe the paths along which (electromagnetic) flows, allows to describe the wave phenomena accounted for by Maxwell's equations on an event-by-event basis [8,[10][11][12][13] in compliance with what one experimentally finds in low-intensity experiments [14,15], also facilitating the understanding of the statistical results typically obtained in quantum optics in the large photon-count limit [16] without the need to involve Fock states in the description. This alternative formulation is actually not that far from the standard formulation of classical electromagnetism, where the corresponding continuity equation favors the definition of a velocity field relating the electromagnetic energy density with its way to spatially distribute, accounted for by the time-averaged Poynting vector [2].…”
Section: Introductionmentioning
confidence: 99%